Visual Perception Among First-Grade Primary School Students Enrolled In And Not Enrolled In Kindergarten (Journal of the College of Basic Education, 2025)
The research problem is defined as knowing the impact of kindergartens on the visual perception of first-grade primary school students, both those enrolled and those not enrolled in kindergarten. The current research aims to measure visual perception among first-grade primary school students, both those enrolled and those not enrolled in kindergarten. The researcher adopted the visual perception test (Younis 2017). The research sample was chosen using a simple random method, amounting to (120) male and female students, both enrolled and not enrolled in kindergarten, from Baghdad government schools affiliated with the Second Rusafa Education Directorate for the academic year 2022/2023. This sample was divided into (60) male and female students enrolled and not enrolled in kindergarten, and (60) female students enrolled and not enrolled. To calculate the reliability of the test, it was applied to a sample of (50) male and female students, and it was reapplied after (14) days had passed from the first application. The reliability of the test was achieved by the test-retest method, as the correlation coefficient between the two tests was (0.83). The apparent validity was extracted. The questionnaire was presented to arbitrators and experts in the fields of educational psychology and kindergarten, and the results showed that all paragraphs of the questionnaire have a high degree of validity. Statistical methods were used through the Statistical Package for the Social Sciences (SPSS) program. The results of the research appeared in the first objective: no differences in visual perception among the sample of students. The second objective: the presence of statistically significant differences between the calculated t-value and the tabular value when comparing the averages of enrolled and non-enrolled students in visual perception in favor of the average of enrolled students.